The influence of soil disturbance on material properties and micro-structure of cement-tretaed soil - M. Makino; T. Takeyama; M. Kitazume (International Association of Lowland Technology, 2015)
The Pneumatic Flow Mixing Method was developed in Japan, in which dredged soft soil is mixed with small amount of chemical binder, usually cement, in a pipe during transporting by compressed air. In some applications, the stabilizied soil is temporary placed at provisional spaced, and is excavated and reclaimed at the final site due to several reasons. In the cases, the stabilized soil in which the chemical reaction has already proceeded is disturbed during the excavation and transportation processes, which causes considerable decrease in the strength at the final state. It is important to investigate the soil disturbance effect for its further applications. The authors have started a research project to investigate the soil disturbance effect on the mechanical properties of cement stabilized soil. The unconfined compression tests were perfomed on three types of laboratory mixed cement stabilized Kaolin clay, stabilized soil without disturbance and disturbed after 3 or 7 days curing. The study revealed that the soil disturbance influenced the stress – strain behavior of the soils considerably. In this paper, a part of the on-going research results is presented as well as the soil preparation and test procedure.